Preventive use of hepatoprotectors yields limited efficacy on the liver toxicity of anti‐tuberculosis agents in a large cohort of Chinese patients. Issue 3 (March 2015) - Wu, Shanshan; Xia, Yinyin; Lv, Xiaozhen; Tang, Shaowen; Yang, Zhirong; Zhang, Yuan; Wang, Xiaomeng; Hu, Daiyu; Liu, Feiying; Yuan, Yanli; Tu, Dehua; Sun, Feng; et al.
Abstract Background and Aims We aimed to explore the effectiveness of preventive usage of hepatoprotectors in patients with tuberculosis (TB) receiving anti‐TB treatment. Methods With stratified cluster sampling strategy, a prospective cohort with 4488 sputum smears positive pulmonary TB patients was established from 52 counties of four regions in China. During anti‐TB treatment, prescriptions of hepatoprotectors were documented in detail, and liver enzymes were routinely monitored. Anti‐TB drug‐induced liver injury (ATLI) was assessed based on liver enzymes following the criteria of American Thoracic Society. The incidence of ATLI between the preventive usage group and reference group was compared by propensity score adjusted Cox proportional hazard analysis. Preexisting diseases, history of liver disease, hepatitis B surface antigen status, primary/re‐treatment of TB, income per year, and liver enzymes before anti‐TB treatment were included in the propensity score model. Results After 6–9 months of follow‐up and monitoring, 4304 patients sustained in our cohort. Two thousand seven hundred fifty‐two (63.9%) patients preventively took hepatoprotectors with a median course of 183 days. Most frequently used drugs were Hu Gan Pian, silymarin, glucurone, and inosine. Two thousand one hundred forty‐four (77.9%) patients took those drugs more than 6 months. Sixty‐nine (2.4%) patients of preventive usage group and 37 (2.5%) of reference group experienced ATLI, respectively. Statistical significances were not found by propensity score analysis for the association between using hepatoprotectors (hazard ratio[HR] = 0.99, 95% confidence interval [CI]: 0.65–1.52), using hepatoprotectors in the whole course (HR = 0.94, 95% CI: 0.60–1.48), using Hu Gan Pians, silymarin, glucurone, and inosine with ATLI occurrence. Conclusions No preventive effect of hepatoprotectors was observed in patients receiving anti‐TB treatment.